Nonlinear electrodynamics AdS black hole and related phenomena in the extended thermodynamics - Kuang, Xiao-Mei; Liu, Bo; Ovguen, Ali (Springer, 2018)
In this paper, we present the analytic solution for Anti-de Sitter-Nonlinear electrodynamics (AdS-NED) black hole in four dimensions. We study tunneling of vector particles from the AdS-NED black hole to find Hawking temperature as well as its thermodynamical properties in usual and extended phase space. Then we explore the properties of pressure-volume criticality by analyzing the phase diagram and its free energy. Finally, we investigate the Joule-Thomson coefficient, in which the inversion curve of warming and cooling are studied, and the ratio between the inverse temperature and critical temperature are computed in the black hole solution.
Keywords: Anti-De-Sitter; P-V Criticality; Phase-Transition; Kerr; Van